2015
DOI: 10.2500/ajra.2015.29.4244
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Postoperative Azithromycin in Patients with Chronic Rhinosinusitis: A Randomized Clinical Trial

Abstract: Treatment with long-term low-dose azithromycin in combination with the conventional therapy could statistically reduce the recurrence rate of CRS symptoms after functional endoscopic sinus surgery, but there was not sufficient evidence to support clinical significance of azithromycin at the investigated dose. Further larger scale trials, along with a longer follow-up period, is needed to evaluate the effectiveness of the therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(101 citation statements)
references
References 23 publications
1
96
1
Order By: Relevance
“…Regarding the mean scores of SNOT-22 questionnaire domains comparison between males and females patients' postoperative results. In our study, there was no significant difference in improvement in the questionnaire score between males and females, the result of our study was in agreement with a randomized controlled trial study in Iran by Amalia et al and a prospective cohort study in the United States by Adappa et al [8,9] . Also, another retrospective cohort study in the United States by Lal et al and a prospective study in Brazil by Bezerra et al [10,11] showed agreement with our results in this comparison.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the mean scores of SNOT-22 questionnaire domains comparison between males and females patients' postoperative results. In our study, there was no significant difference in improvement in the questionnaire score between males and females, the result of our study was in agreement with a randomized controlled trial study in Iran by Amalia et al and a prospective cohort study in the United States by Adappa et al [8,9] . Also, another retrospective cohort study in the United States by Lal et al and a prospective study in Brazil by Bezerra et al [10,11] showed agreement with our results in this comparison.…”
Section: Discussionsupporting
confidence: 93%
“…The reasons for exclusion are listed in Figure . Finally, 10 studies were included for qualitative synthesis and nine studies for quantitative synthesis . Characteristics of the included studies are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 31 studies were considered to be duplicates from the same cohort, and an additional 53 failed to meet inclusion/exclusion criteria. The final study list included 40 unique patient cohorts published from 2008 to 2016 and representing institutions from North America (n = 14), Europe (n = 12), Middle East (n = 6), Australia (n = 3), Asia (n = 3), and South America (n = 2) . The majority of studies were prospective observational cohorts (n =2 3), with the remainder being surgical arms from randomized clinical trials (n = 7), retrospective cohorts (n = 7), or case‐control studies (n = 3).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies examined the association of preoperative CT scores with SNOT‐22 change scores, with one finding a positive correlation and the other two showing no impact . Sex and age were each evaluated by three studies with none showing any association. Other factors of interest included allergy, asthma, revision surgery, depression, tobacco use, preoperative SNOT‐22 score, and length of follow‐up.…”
Section: Resultsmentioning
confidence: 99%